Adjusting the Anisotropy of 1D Sb2Se3 Nanostructures for Highly Efficient Photoelectrochemical Water Splitting. Issue 14 (23rd January 2018) - Yang, Wooseok; Ahn, Jihoon; Oh, Yunjung; Tan, Jeiwan; Lee, Hyungsoo; Park, Jaemin; Kwon, Hyeok‐Chan; Kim, Juran; Jo, William; Kim, Joosun; Moon, Jooho
Abstract: Sb2 Se3 has recently spurred great interest as a promising light‐absorbing material for solar energy conversion. Sb2 Se3 consists of 1D covalently linked nanoribbons stacked via van der Waals forces and its properties strongly depend on the crystallographic orientation. However, strategies for adjusting the anisotropy of 1D Sb2 Se3 nanostructures are rarely investigated. Here, a novel approach is presented to fabricate 1D Sb2 Se3 nanostructure arrays with different aspect ratios on conductive substrates by simply spin‐coating Sb‐Se solutions with different molar ratios of thioglycolic acid and ethanolamine. A relatively small proportion of thioglycolic acid induces the growth of short Sb2 Se3 nanorod arrays with preferred orientation, leading to fast carrier transport and enhanced photocurrent. After the deposition of TiO2 and Pt, an appropriately oriented Sb2 Se3 nanostructure array exhibits a significantly enhanced photoelectrochemical performance; the photocurrent reaches 12.5 mA cm −2 at 0 V versus reversible hydrogen electrode under air mass 1.5 global illumination. Abstract : A highly efficient Sb2 Se3 ‐based photocathode for water splitting is demonstrated by adjusting the anisotropy of 1D nanostructures. A simple modulation of the Sb‐Se precursor solution enables the desired orientation control of the Sb2 Se3 nanostructures, consequently resulting in fast carrier transport and enhanced photocurrent. The Sb2 Se3 ‐based photocathode exhibits a remarkable photocurrent of 12.5 mA cm −2 at 0 V versus reversible hydrogen electrode.